Improving Physical Learning Results through the Problem Posing Method in State 4 Pekanbaru High School - Nurliana, Nurliana (Proceedings of the UR International Conference on Educational Sciences, 2018)
This research is based on still many students who have not reached the complete criteria for rigid body equilibrium material. Efforts to improve learning outcomes, an effective method is needed so that students are serious and try to solve problems in the learning process. The problem-posing method is a step to improve the results of teaching and learning activities. For this reason, the research aims to find out whether or not there is an influence of the problem-posing method on students learning and activity in learning physics. This research was carried out in 2 cycles from January to April 2016. The subjects of this study were students of class XI IPA 4 of SMA Negeri 4 Pekanbaru totaling 38 people. Research data was obtained through observation and evaluation tests. The results of the analysis showed that the learning activity of students in cycle II showed an increase compared to cycle I. Increasing activeness in asking was 54.8%, the ability to make questions 66.9%, the ability to solve problems made 63.7%, the ability to solve problems made by his friend 66.9%, and the ability to convey ideas 55.6%. The average class of each cycle also increased, in the first cycle was 82.1 and the second cycle was 86.74. Classical learning completeness in cycle I is 76.3% and cycle II increases to 92.1%. The results of the research analysis show that the problem posing method of learning is more preferred by students so that it can improve learning for students.